Hand hygiene quality indicator in Nursing home Ljubljana Slovenia - Medjedovic, Sabina; Kovacic, Martina Dimnik; Toroman, Dragana (Polish Journal of Public Health, 2026)
Introduction. Hand hygiene is a key indicator of quality and safety in long-term care facilities. This study aimed to assess compliance with hand hygiene practices in a nursing care home for older adults in 2025. Methods. An observational audit was conducted from 1 July to 27 August 2025 across six departments of the care home, following the World Health Organization (WHO) “Five Moments for Hand Hygiene” methodology. Observations were performed openly, and healthcare personnel were aware that hand hygiene monitoring was taking place. The minimum required number of 424 hand hygiene opportunities was defi ned according to institutional standards issued by the Ministry of Health. The target number was not based on a statistical power calculation but followed predefi ned quality assurance requirements. Results. Overall hand hygiene compliance was 84.76%, with the highest adherence among physiotherapists, occupational therapists, and social workers (100%), followed by healthcare professionals with compliance above 80%, and the lowest among cleaning staff (68.75%). A total of 433 hand hygiene opportunities were observed. Overall compliance ratio was 367 out of 433 (84.76%), with a 95% Wilson confi dence interval of 81.07% to 87.84%. Discussion. The results indicate good overall compliance with hand hygiene practices, although improvements are possible regarding disinfectant accessibility and the regularity of monitoring. These fi ndings may inform quality improvement efforts aimed at strengthening resident safety and care quality.